Corporate finance - Ross, Stephen A.; Westerfield, Randolph W.; Jaffe, Jeffrey; Jordan, Bradford D. (New York, NY : McGraw-Hill Education, 2019)
A highly reliable, easy-to-use homework and learning management solution that embeds learning science and award-winning adaptive tools to improve student results. Emphasizes the modern fundamentals of the theory of finance, while providing contemporary examples to make the theory come to life. The authors aim to present corporate finance as the working of a small number of integrated and powerful intuitions, rather than a collection of unrelated topics. They develop the central concepts of modern finance: arbitrage, net present value, efficient markets, agency theory, options, and the trade-off between risk and return, and use them to explain corporate finance with a balance of theory and application.
Part I. Overview -- Part II. Valuation and capital budgeting -- Part III. Risk -- Part IV. Capital structure and dividend policy -- Part V. Long-term financing -- Part VI. Options, futures, and corporate finance -- Part VII. Short-term finance -- Part VIII. Special topics.
BBS
Keywords: Corporations -- Finance; Corporations -- Finance; Business & finance